The synthesis of gold nanoparticles and its extensive applications - Abu Bakar, Faridah; Zayadi, Rabiatul Adawiyah (Penerbit Uthm, 2019)
Gold nanoparticles (GNP) have been extensively investigated within these few decades for their unique electronic, optical and catalytic properties. Nanosized gold or GNP exhibits different physico-chemical properties from bulk gold where GNP exhibits various vivid colors depending on the particle size and shape. GNP is highly reactive, and highly stable against oxidation, making it an exciting material for interdisciplinary research especially in photocatalysis and biomedical field. This chapter provides an insight on the historical discovery of GNP, and its unique properties as opposed to bulk and gold cluster, together with its applications in the advancing world of science and technology. Although variety of research on GNP had been reported especially on its biomedical applications there are still many setbacks and parameters that need to be tuned. The lack of sufficient stability of GNP due to its facile aggregation, and its biocompatibility concern to be used within living cells have impeded development of its applications in the real world. Also discussed in this chapter are the conventional and green methods employed by scientists in the synthesis for stable and biocompatible GNP. This chapter also concludes with a short overview on the future scientific miracles we may achieve with GNP.